SOSIALISASI PEMBELAJARAN HIGHER ORDER THINGKING SKILL HOTS UNTUK GURU SMA NEGERI 1 SIPORA KABUPATEN KEPULAUAN MENTAWAI - Zuraida Khairani; Eva Fitrianti; Novi Fitriani; Marzuki Saogo; Sindi Irawati (LPPM Universitas Ekasakti, 2024)
The challenges of the 21st century require students to have the ability to analyse, solve problems, and creativity through Higher Order Thinking Skills (HOTS) based learning. Learning implemented in schools must be able to develop critical thinking, creative thinking, collaboration and communication skills. The main purpose of HOTS is to improve learners' thinking ability at a higher level, especially in receiving various types of information, solving problems, arguing well, and making decisions in complex situations. Through HOTS, learners are expected to learn new things and apply them to different situations. The methods used included lectures, questions and answers, and practice in preparing HOTS-based syllabus and lesson plans. The resource person provided material on the concept of HOTS and LOTS based on Bloom's Taxonomy, as well as how to integrate them in the syllabus and lesson plans. The results of this activity show that teachers have understood the preparation of HOTS-based syllabus and lesson plans, although there are still some obstacles in applying the HOTS concept.